2013
DOI: 10.1097/rhu.0b013e3182848037
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatology Practice Profiles in Teaching and Community Settings in Puerto Rico

Abstract: Several differences were found in the profile of demographic parameters, diagnoses, medical visits, and rheumatologic procedures between patients seen at the University of Puerto Rico Medical Sciences Campus rheumatology practice and 3 community-based practices. Efforts may be required to diversify and increase the exposure of rheumatology fellows to patients with conditions commonly seen at the community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…A slightly larger UK study in 2000 similarly showed a high rate of osteoarthritis compared to inflammatory arthritis (Guilar et al., 2000). A similar sized study to the current one from Puerto Rico in 2003 demonstrated similar rates of clinic visits for diseases as this study, with connective tissue disease and inflammatory arthritis making up a majority of cases (Negrón et al., 2013). Their study was unique in that they compared visit rates in community and academic practices, with significant differences noted; while inflammatory arthritis was the number one condition observed in both setting, more inflammatory disease was seen in the academic practices while osteoarthritis was more common in the community practice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A slightly larger UK study in 2000 similarly showed a high rate of osteoarthritis compared to inflammatory arthritis (Guilar et al., 2000). A similar sized study to the current one from Puerto Rico in 2003 demonstrated similar rates of clinic visits for diseases as this study, with connective tissue disease and inflammatory arthritis making up a majority of cases (Negrón et al., 2013). Their study was unique in that they compared visit rates in community and academic practices, with significant differences noted; while inflammatory arthritis was the number one condition observed in both setting, more inflammatory disease was seen in the academic practices while osteoarthritis was more common in the community practice.…”
Section: Discussionsupporting
confidence: 78%
“…However, there is limited data available that currently describes rheumatology practices. A review of the literature suggests this work has been done, but only intermittently over time, with no significant review in nearly 10 years (Blechman et al., 1977; Boulos et al., 2000; Guilar et al., 2000; Healey et al., 1988; Negrón et al., 2013). Yet, the practice of rheumatology has seen change over that time, particularly with the ongoing proliferation of new advanced biologic therapies.…”
mentioning
confidence: 99%
“…The recognition of arthritis, tenosynovitis, tendinopathy, enthesitis, bursitis, myositis, or nerve entrapment, which is so important in steering the clinician toward a sensible differential diagnosis, requires knowledge and skills in clinical anatomy. A prime example is the diagnosis and understanding of the regional pain syndromes, which comprise 13–30% of a rheumatologist's workload in the outpatient setting () and affect approximately 5% of individuals in the general population (). Unfortunately, clinical anatomy in rheumatology training has too often been taught superficially and on an ad hoc basis, i.e., shoulder anatomy as it relates to shoulder pain, the lumbar spine as it relates to low back pain, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A deeper knowledge of clinical anatomy can only help in the care of the 7 to 30% of patients with regional pain syndromes seen in outpatient rheumatology practices (8)(9)(10)(11)(12). Furthermore, and probably just as important, is our belief that a deeper knowledge of the involved structures may improve the clinical evaluation of patients with systemic rheumatic diseases in whom bone landmarks, joints, tendons, entheses, bursae, vessels, and nerves are often involved (13).…”
mentioning
confidence: 99%